The effects of cross-examination on children's reports of neutral and transgressive events - Fogliati, Rhiannon (Legal and criminological psychology, 2014)
Purpose In many jurisdictions child witnesses who testify in court about their own sexual abuse are cross-examined by a defence attorney. Children find this process to be distressing, and despite recent child-focussed modifications to other aspects of the legal process, cross-examination has remained largely unaltered. This lack of modification is due, in part, to the assumption that cross-examination promotes truthful testimony (Wigmore, 1974 Evidence in trials at common law). However, little empirical research has investigated the effects of cross-examination questions on children's reports of neutral and transgressive events. To examine these effects a laboratory-based study was conducted. Method One hundred and twenty kindergarten (M = 6 years) and grade 2 (M = 8 years) students participated individually in a staged event. Children witnessed an adult commit a transgression and were then interviewed twice about it. Children first underwent a direct-examination interview followed by either a direct- or cross-examination interview. Results Children's reports of neutral events were significantly less accurate in Interview 2 cross-examination, than they were in Interview 1 direct-examination, whereas children interviewed twice with direct-examination were equally accurate in Interviews 1 and 2. Furthermore, children whose second interview involved cross-examination were less accurate in their reports of neutral events than were children whose second interview was a direct examination. Cross-examination also affected some children's disclosures of a witnessed transgression. More of the older children provided truthful disclosures of the transgression in the initial direct examination compared with the Interview 2 cross-examination. Conclusions Findings suggest that cross-examination as used in this study may not be the most effective procedure for eliciting truthful testimony for both neutral and transgressive events from children aged between 5 and 8 years.